How will NATO's non-nuclear members handle the UN's ban on nuclear weapons?. (4th May 2017) - Sauer, Tom
ABSTRACT: The start of multilateral negotiations for a nuclear ban treaty will lead to renewed discussions about the role of nuclear weapons in NATO. It is an opportunity to review the alliance's nuclear weapons policy in light of this new international dynamic. NATO's nonnuclear members should help denuclearize the organization or at least push nuclear weapons back to the national realm.